Obstetric violence: A literature review (Research, Society and Development, 2023)
Introduction: Obstetric violence is a worldwide phenomenon that has been increasingly discussed in the scientific community and in society in general. This is a type of gender-based violence that occurs during childbirth and the process of caring for women during the gestational period, which may include actions or omissions by health professionals that harm the woman's physical and mental health. Objective: To analyze obstetric violence from a public health perspective, considering its impacts on women's health and the policies and strategies that can be adopted to prevent it. Methodology: The proposed review adopts a descriptive qualitative approach, in a narrative review format. Results and Discussion: All studies emphasize the need for humanized and respectful obstetric care, which takes into account women's choices and preferences and avoids situations of obstetric violence. Furthermore, they highlight the importance of training and raising awareness among health professionals and implementing public policies that can guarantee women's right to a safe and respectful birth. Final Considerations: Actions that promote the prevention of obstetric violence and respect for women's human rights must be adopted in all spheres of maternal health care, including prenatal care, childbirth and postpartum care. It is essential that health professionals, managers, governments and society in general are involved in this fight to guarantee women's health and rights.